2016
DOI: 10.22146/jkap.9934
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Development Disparities Inter Districts/ City in Special Region of Yogyakarta (DIY) Province 2003-2013

Abstract: One of the objectives of regional economic development is to increase the economic sector, in which the increasing of economics sector will be beneficial for society. This indicator is important to recognize the condition of the economy in particular region

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…In the LQ method, the mean value of economic sector from year the 2010-2016 show extrem value from 0.16 (Provision of Accommodation and Drinking) to 6.13 (Water Supply, Waste Management, Waste and Recycling). This information accordance with research result of Nurpita and Nastiti (2016) that concluded that Daerah Istimewa Yogyakarta is included in the category of developing regions and has a fast growth rate. However, development in districts has a greater degree of disparity.…”
Section: Klassen Typologysupporting
confidence: 91%
See 1 more Smart Citation
“…In the LQ method, the mean value of economic sector from year the 2010-2016 show extrem value from 0.16 (Provision of Accommodation and Drinking) to 6.13 (Water Supply, Waste Management, Waste and Recycling). This information accordance with research result of Nurpita and Nastiti (2016) that concluded that Daerah Istimewa Yogyakarta is included in the category of developing regions and has a fast growth rate. However, development in districts has a greater degree of disparity.…”
Section: Klassen Typologysupporting
confidence: 91%
“…While in Tanggamus Regency still remind the agricultural sector. The results of the study by Nurpita and Nastiti (2016) conclude that Daerah Istimewa Yogyakarta is included in the category of developing regions and has a fast growth rate. However, development in districts has a greater degree of disparity.…”
Section: Introductionmentioning
confidence: 96%
“…Klassen's typology can be applied to determine sectoral contributions, as shown by [8], [9], [10], [11], [12], and [13]. Typology can make used to determine inequality, as shown by the studies of [14], [15], and [16]. [17] on economic and income inequality between regions.…”
Section: Figure 2 the Growth Rate Of Gdp Per Capita 2014-2019mentioning
confidence: 99%
“…Regional economic growth and per capita income serve as the two key indicators used by the Klassen typology to classify regions. According to Nurpita and Nastiti (2016), the regions identified in this study can be categorized into four classifications the rapid growth region (high growth and high income), the depressed region (high income but low growth), the developing region (high growth but low income), and the relatively backward region (low growth and low income)-by specifying the average economic growth as the vertical line and the average income per capita as the horizontal line. Note: ri: the economic growth rate of district/city i in Kedungsepur r: average of the economic growth rate of all districts/cities in Kedungsepur yi: GRDP per capita of district/city i in Kedungsepur y: average GRDP per capita of all districts/cities in Kedungsepur…”
Section: Klassen Typologymentioning
confidence: 99%